Mass Spectrometry‐Based Bottom‐Up Proteomics: Sample Preparation, LC‐MS/MS Analysis, and Database Query Strategies. (1st November 2016) - Wither, Matthew J.; Hansen, Kirk C.; Reisz, Julie A.
Abstract: Recent technological advances in mass spectrometry (MS) have made possible the investigation and quantification of complex mixtures of biomolecules. The exceptional sensitivity and resolving power of today's mass spectrometers allow for the detection of proteins and peptides at low femtomole quantities; however, these attributes demand high sample purity to minimize artifacts and achieve the highest degree of biomolecule identification. Tissue preparation for proteomic studies is particularly challenging due to their heterogeneity in cell type, presence of insoluble biomaterials, and wide diversity of biomolecules. The workflow described herein details sample preparation from tissues through protein extraction, proteolysis, and purification to generate peptides for MS analysis. Increased peptide resolution and a corresponding increase in protein identification is accomplished using polarity‐based fractionation (C18 resin) at the peptide level. Additionally, approaches to instrument set up, including the use of nanoscale liquid chromatography and quadrupole Orbitrap MS, along with database searching, are described. © 2016 by John Wiley & Sons, Inc.